ILLNESSES AND DEATH T.G.SHEVCHENCA - Геник, С. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Selfless life and creation of fortress son, this of genius Ukrainian poet must always stand before our eyes, before the eyes of our children, grandchildren and great-grandchildren, while Ukraine will not become Ukrainian.